MicroRNAs Profiling Identifies miR-125a and Its Target Gene Wnt2 in Skins of Different Haired Rabbits - Chen, Yang; Zhao, Bohao; Liu, Ming; Wang, Jingyi; Qiu, Xiaoqing; Zhu, Cigen; Wu, Xinsheng (Frontiers in Genetics, 2018)
MicroRNAs (miRNAs) play critical roles in the control of skin and hair follicle development, epidermal homeostasis and pigmentation. However, the roles of miRNAs in the skins of rabbits with different hair types are unclear. In this study, we profiled miRNAs in the skins of long and short haired rabbits by Illumina deep sequencing. The dataset was compared with known mammalian miRNAs in miRBase 21.0. In total, 118 miRNAs were found to be differentially expressed between the two different rabbit types, of which 94 were upregulated, and 24 were downregulated in the skin of short haired versus long haired rabbits. The expression levels of five randomly selected miRNAs detected by quantitative real-time PCR indicated that the expression patterns were consistent with Illumina sequencing results. What’s more, bioinformatics analysis showed that miR-125a might target Wnt2, an important modulator for hair follicle development. To test whether Wnt2 is a target of miR-125a, luciferase reporter vector (pMir-report-Wnt2-3'-UTR-WT) and its substitution mutant (pMir-report-Wnt2-3'-UTR-MUT) were constructed. Co-transfection and reporter enzyme assays showed that compared with control (miR-125a NC transfection), miR-125a mimics transfection significantly inhibited the reporter luciferase activities expressed by pMir-report-Wnt2-3'-UTR-WT, while transfection of miR-125a inhibitors increased reporter enzyme activities. RT-PCR and Simple Western analysis found that Wnt2 mRNA and protein levels were induced or repressed by miR-125a overexpression or inhibition, respectively. Moreover, the mRNA expression levels of genes in Wnt signaling pathway, such as CTNNB1, LEF-1, PPARD and TGFB1, were also significantly changed (P<0.05), consistent with Wnt2. It indicated that the regulation of Wnt2 expression by miRNAs may depend on the transcriptional degradation. The results will help to further understand the role of miRNAs in hair follicle development and the genetic mechanism underlying hair length phenotype.